2011
DOI: 10.1186/1477-7827-9-114
|View full text |Cite
|
Sign up to set email alerts
|

Decreased levels of genuine large free hCG alpha in men presenting with abnormal semen analysis

Abstract: BackgroundThe pregnancy hormone human chorionic gonadotropin (hCG) and its free subunits (hCG alpha, hCG beta) are produced in the male reproductive tract and found in high concentrations in seminal fluid, in particular hCG alpha. This study aimed to elucidate changes in peptide hormone profiles in patients showing abnormal semen analyses and to determine the genuineness of the highly abundant hCG alpha.MethodsSeminal plasma was obtained from 45 male patients undergoing semen analysis during infertility workup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Moreover, oligozoospermia was characterized by reduced seminal plasma hCG levels compared with normozoospermic men. 4 …”
Section: Seminal Peptides and Semen Parametersmentioning
confidence: 99%
“…Moreover, oligozoospermia was characterized by reduced seminal plasma hCG levels compared with normozoospermic men. 4 …”
Section: Seminal Peptides and Semen Parametersmentioning
confidence: 99%
“…Semen abnormalities are a form of male infertility which present in a variety of ways and may prevent the sperm from achieving fertilization (1)(2)(3)(4). Previous studies have shown that there are several causes of abnormal semen, including infection with sexually transmitted diseases (STDs), retrograde ejaculation and an inability of the ejaculate to clot properly, all of which can significantly affect male fertility.…”
Section: Introductionmentioning
confidence: 99%
“…It is normally secreted at high levels in pregnant women to perform many endogenous functions, while its level is absent or very low in men [9,10,20,21]. It plays an important role in spermatogenesis via LH receptor [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, highest level of hCG was found in 15-20% of advanced seminomatous GCT and in 40% of advanced nonseminomatous GCT [1]. Although some testis disorders or cancers, other than TC, cause elevation of hCG levels, serum hCG level is still essential in the diagnosis of TC, especially when TC is responsible for most of testicular malfunctions [1,4,12,20]. LDH, which is produced by various types of tissues in the human body, is considered a nonspecific marker [5].…”
Section: Discussionmentioning
confidence: 99%